Investigation of forced convection heat transfer for Al2O3 nanofluids in different base mixture - Nur Ashikin, Usri (2016)
In the thermal engineering application, suspension of nanoparticles in conventional fluid has positive potential in enhancing the convective heat transfer performance. Nanofluids are developed to meet the challenges of improving the efficiency of the cooling system subsequently minimizing the energy waste. This thesis aims to investigate the forced convection heat transfer for Al2O3 nanofluids in different ratios of water (W) and ethylene glycol (EG) base mixture at different working temperatures. The Al2O3 nanofluids are formulated using the two-step method for three different base mixture with volume ratio of 60:40, 50:50 and 40:60 (W:EG). The volume concentration varies between 0.2 to 1.0 %. The properties measurement of thermal conductivity and viscosity of nanofluids are conducted using scientific laboratory equipment. The forced convection experiments are conducted using modified convection experimental setup under constant heat flux conditions for operating temperatures of 30, 50 and 70 °C at Reynolds numbers from 3,000 to 25,000. The enhancement of viscosity for nanofluids decrease with the increment percentage of ethylene glycol. Meanwhile, thermal conductivity have positive enhancement as the percentage of ethylene glycol increases. The forced convection results indicate that with increased volume concentrations, the heat transfer coefficient is enhanced compared to its base fluid at all designated temperatures. The enhancement of nanofluids is observed to be improved further with the increase of temperature. The effect of different base mixture ratios display that nanofluids in 60:40 (W:EG) base mixture have the highest percentage of performance with 24.6 % enhancement at 1.0 % volume concentration and temperature of 70 °C. The increment of volume concentration for nanofluids shows a slight rise in friction factor and pressure drop. As a conclusion, the thermo-physical properties and the forced convection heat transfer for nanofluids in various base mixture shows that volume concentrations, base fluid, and temperature influences the enhancement of heat transfer. The Al2O3 nanofluids with 1.0 % volume concentration in 60:40 (W:EG) base mixture are recommended for various applications in heat transfer.